STUDY ON EFFECTIVE MARKETING STRATEGIES TO INCREASING ACTIVE USERS OF THE SITRAB APPLICATION OF PUPR SERVICE OF WEST ACEH - Jhony Howord; Cut Mega Putri (RADJA PUBLIKA, 2023)
In today's digital era, it is an obligation for the Government to provide information digitally and easily accessible to the public. However, many applications developed by the Government do not last long in the market due to the lack of an effective marketing strategy. Therefore, this research is expected to find out effective marketing strategies to increase the number of active application users. The case study was carried out on the application of the West Aceh Spatial Information System (SITRAB) which is an application under the auspices of the West Aceh Public Works and Spatial Planning (PUPR) office. The method used by the author in this study is a qualitative method. The results of this study indicate that effective marketing strategies to increase the number of active application users include promotions through social media, marketing personalization, and viral marketing. In addition, this study also shows that the factors that influence application adoption include ease of use, accuracy of information, and features offered. This research is expected to provide benefits for application developers in increasing the number of active application users through an effective marketing strategy.